In Quest of a Shared Planet Negotiating Climate from the Global South - Khan, Naveeda (Fordham University Press, 2023)
Based on the author's eight years of fieldwork with the United Nations-led Conference of Parties (COP), In Quest of a Shared Planet offers an illuminating first-person ethnographic perspective on climate change negotiations. Focusing on the Paris Agreement, anthropologist Naveeda Khan introduces readers to the only existing global approach to the problem of climate change, one that took nearly thirty years to be collectively agreed upon. She shares her detailed descriptions of COP21 to COP25 and growing understanding of the intricacies of the climate negotiation process, leading her to ask why countries of the Global South invested in this slow-moving process and to explore how they have maneuvered it. With a focus on the Bangladeshi delegation at the COPs, Khan draws out what it means to be a small, poor, and dependent country within the negotiation process. Her interviews with negotiators within country delegations uncover their pathways to the negotiating tables. Through observations of training sessions of negotiators of the Global South, Khan seeks to reveal understandings of what is or is not achievable within negotiated texts and the power of deal-making and deferrals. She profiles individuals who had committed themselves to the climate negotiation process, moving between the Secretariat, Parties, activists, and the wider UN system to bring their principles, strategies, emotions, and visions into view. She explores how the newest pillar of climate action, loss and damage, emerged historically and how developed countries attempted to control it in the process. Khan suggests that we understand the Global South's pursuit of loss and damage not only as a politics of forcing the issue of a conjoined future upon the Global North, but as a gift to the youth of the world to secure that future. With this book Khan hopes to rekindle an older way of doing politics through the tenets of diplomacy upheld by the UN that have been overshadowed of late by the politics of confrontation. She stresses that while the tension between efforts of equity and solidarity and global economic competition, which have run through the negotiation process, might undercut the urgency to carry out climate mitigation, it needs to be addressed for meaningful and sustainable climate action. Deeply insightful and highly readable, In Quest of a Shared Planet is a stirring call to action that highlights the key role responsive and active youth have in climate negotiations. It is an invitation not only to understand the climate negotiation process, but also to navigate it (for those planning to attend sessions themselves) and to critique it-with, the author hopes, sympathy and an eye to viable alternatives. In Quest of a Shared Planet: Negotiating Climate from the Global South is available from the publisher on an open-access basis.